More on the Postmodernism of Rosler’s: The Bowery in Two Inadequate Descriptive Systems - Sadeghzadegan, Majid; Safari Monfared, Mahdi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Martha Rosler's textual-visual masterpiece The Bowery in Two Inadequate Descriptive Systems is in possession of numerous postmodernist dimensions. The current study, therefore, is intended to elucidate how The Bowery benefits from postmodernist aesthetics and rhetoric. It will argue that such postmodernist elements as irony, paradox, and parody lie at the heart of Rosler's photo-text art. To that end, the article will employ Linda Hutcheon's postmodernist terminology and theories as the underlying theoretical framework. Analysing The Bowery through the lens of the said theorist's postmodernist approach and vocabulary, the essay will assert that Rosler's premises resonate strongly with Hutcheon's theories. Moreover, generically viewed, The Bowery will be deemed to be a complex of postmodern photography and social documentary practices. The current article will attempt to re-evaluate and thus furnish a fresh reading of The Bowery in light of its postmodern conceptual and photographic elements.